Cultural transmission : psychological, developmental, social, and methodological aspects - Schönpflug, Ute (Culture and psychology, 2008)
Cultural Transmission covers psychological, developmental, social, and methodological research on how cultural information is socially transmitted from one generation to the next within families. Studying processes of cultural transmission may help analyze the continuity or change of cultures, including those that have to cope with migration or the collapse of a political system. An evolutionary perspective is elaborated in the first part of the book; the second takes a cross-cultural perspective by presenting international research on development and intergenerational relations in the family; the third provides intra-cultural analyses of mechanisms and methodological aspects of cultural transmission. Made up of contributions by experts in the field, this source book is intended for anyone with interests in cultural issues - especially researchers and teachers in disciplines such as psychology, social and behavioral sciences, and education - and for applied professionals in culture management and family counseling, as well as professionals dealing with migrants.
Keywords: Socialization; Ethnopsychology; Cognition and culture; Learning : Social aspects; Learning, Psychology of